2021
DOI: 10.1002/adem.202001000
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Corrosion Resistance and Antibacterial Performance of Novel Fe–xCu Biomedical Alloys Prepared by Selective Laser Melting

Abstract: Antibacterial Fe-xCu biomedical alloys are designed to have a satisfactory biodegradation rate compared with pure iron. Fe-xCu (x ¼ 0, 1.5, 2.3, 7.8, and 10.1 wt%) alloys are produced by selective laser melting (SLM). Alloying with Cu has a significant influence on the grain size, hardness, biodegradation rate, and antibacterial performance of SLMed Fe-xCu alloys. Increasing Cu content decreases the grain size and increases the hardness. SLMed Fe-1.5Cu, Fe-2.3Cu, and Fe-10.1Cu have degradation rates similar to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 46 publications
2
34
0
Order By: Relevance
“…Cu and Fe have the standard potential of +0.34 V SHE [ 20 ] and −0.44 V SHE [ 5 ], respectively, which leads to the micro-galvanic corrosion effect between Cu-rich precipitation and Fe matrix in Fe-Cu alloy, increasing the corrosion rate. The release of Cu 2+ with corrosion progressing can produce the desired antibacterial effect, as was recently confirmed by Guo et al [ 21 ], who used selective laser melting to produce antibacterial Fe-xCu alloys having a satisfactory biodegradation rate compared to pure iron.…”
Section: Introductionmentioning
confidence: 69%
See 4 more Smart Citations
“…Cu and Fe have the standard potential of +0.34 V SHE [ 20 ] and −0.44 V SHE [ 5 ], respectively, which leads to the micro-galvanic corrosion effect between Cu-rich precipitation and Fe matrix in Fe-Cu alloy, increasing the corrosion rate. The release of Cu 2+ with corrosion progressing can produce the desired antibacterial effect, as was recently confirmed by Guo et al [ 21 ], who used selective laser melting to produce antibacterial Fe-xCu alloys having a satisfactory biodegradation rate compared to pure iron.…”
Section: Introductionmentioning
confidence: 69%
“…The corrosion potential ( E corr ) and corrosion current density ( i corr ) were evaluated by the Tafel extrapolation method [ 28 , 29 ]. The polarization curve of the microwave-sintered pure Fe had an obvious current platform in the anode region, as shown in Figure 4 a, which indicated that the pseudo-passivation film might be formed on the surface, affecting the corresponding degradation rate [ 21 ]. However, for the microwave-sintered Fe-8Cu samples, the anode branch current of polarization curve increased steadily with increasing potential.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations